Designing Android-Based Smart Apps Creator Learning Media to Improve Critical Thinking Skills - Fricticarani, Ade; Nimpagaritse, Stève; Fauzansyah, Tengku Ahmad; Abraham; Rahmadani, Kurniati; Lelfita (Vocational: Journal of Educational Technology, 2025)
The rapid evolution of technology in education necessitates innovative approaches to enhance critical thinking skills, a vital competency in the 21st century. This study aims to design and evaluate Android-based learning media using the Smart Apps Creator (SAC) platform, targeting the improvement of critical thinking skills among students in the educational technology course in the information technology education study program of the faculty of teacher training and education at Bina Bangsa University, Banten, Indonesia. The research adopts the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation phases. The developed learning media consists of interactive components, including a main page, learning objectives, usage instructions, educational materials, and evaluation exercises. The media was evaluated by four expert validators for content and media validity, yielding scores of 93% and 91%, respectively, categorized as "very valid." Practicality was assessed through student feedback, with an average score of 89.5%, indicating "very practical" usability. Effectiveness was measured through pre-test and post-test evaluations, showing a significant improvement in critical thinking skills with an average effectiveness score of 90.5%. These results highlight the learning media's capability to enhance engagement and foster critical thinking skills effectively. The study underscores the potential of SAC-based applications as a scalable solution for integrating interactive and student-centered learning tools into higher education. Future research could explore the application of such media across various educational contexts and its impact on other 21st-century competencies.